Education 3640. Problems and issues in special education. Summary. - Nesbit, W. C. (Wayne C.), 1943- (Teacher); Karagianis, Leslie D. (Teacher); Memorial University of Newfoundland. Division of Educational Technology (Producer)
Dr. Karagianis summarizes the course content of Education 3640.